The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/jsfa.9655
|View full text |Cite
|
Sign up to set email alerts
|

Quality, functional and sensory evaluation of pasta fortified with extracts from Opuntia ficus‐indica cladodes

Abstract: BACKGROUND: The stems of Opuntia ficus-indica, known as cladodes, are a rich source of soluble fibers, which makes them an important candidate for the production of functional foods. Tagliatelle of durum wheat fortified with Opuntia cladode extract (OCE) at different levels of addition (10-30%, v/w) was prepared on a laboratory scale and quality characteristics and sensory acceptability were assessed. RESULTS:The main quality parameters (optimal cooking time, swelling index, cooking loss, dry matter) and senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The optimal cooking time and water absorption did not show significant difference ( p > .05) between the evaluated treatments (T0, T120‐T, and T120‐M) for each pasta sample (Figure 3). Optimal cooking time is defined as the time necessary for the complete disappearance of the white central core of the pasta, indicating the complete gelatinization of the starch (Attanzio et al., 2019; Borneo & Aguirre, 2008). According to Casagrandi, Canniatti‐Brazaca, Salgado, Pizzinato, and Novaes (1999), cooking time varies according to the size and shape of the pasta.…”
Section: Resultsmentioning
confidence: 99%
“…The optimal cooking time and water absorption did not show significant difference ( p > .05) between the evaluated treatments (T0, T120‐T, and T120‐M) for each pasta sample (Figure 3). Optimal cooking time is defined as the time necessary for the complete disappearance of the white central core of the pasta, indicating the complete gelatinization of the starch (Attanzio et al., 2019; Borneo & Aguirre, 2008). According to Casagrandi, Canniatti‐Brazaca, Salgado, Pizzinato, and Novaes (1999), cooking time varies according to the size and shape of the pasta.…”
Section: Resultsmentioning
confidence: 99%
“…In recent times, Opuntia ficus-indica cladodes have been exploited for nutraceutical and health-promoting purposes since they exert a plethora of beneficial effects on both lipid and glucose dysmetabolism [ 15 , 16 , 17 , 18 , 19 , 20 ]. Conversely, much less attention has been paid to the fruit, hallmarked by a phytochemical fingerprint different from the cladode one.…”
Section: Introductionmentioning
confidence: 99%
“…One study found no effect on the in vitro starch digestion in pasta prepared with fine bran 10–30% [ 27 ]. Vegetables have been added to pasta for many years with two studies showing low pasta GI with added vegetable pulps [ 131 ] supported by the in vitro studies [ 77 , 79 ]. The other ingredients added to pasta listed in Table 2 seem not to have been evaluated in human clinical trials (gums, debranning fractions, wheat embryo, herbs, protein extracts) so more evaluation is needed.…”
Section: Resultsmentioning
confidence: 99%